The Repentance Bath of Abah Anom's Inabah: A Hydrotherapy for Drug Addicts in Muslim Society - Nurhamzah Cahyo Setio; Asep Harry Hernawan; Rusman Rusman; Chiedu Eseadi (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2023)
The repentance bath of Abah Anom's Inabah is used as a form of hydrotherapy, and many scholars admit that it is effective at treating drug addiction. There are, however, many others who do not fully understand the concept of the repentance bath and its implementation process. In this article, we described the concept and implementation of Abah Anom's Inabah. This study also examined the effects of repentance bath on patients suffering from drug addiction. The study used a qualitative descriptive research methodology with a phenomenological perspective. The results of this research conceptualized Abah Anom's Inabah as a form of internal and external hydrotherapy for treating drug addicts in accordance with the postulations of the Qur'an and Hadith, such as water being the primary source of life for God's creatures, bath as a way of purifying both physical and mental states, water being beneficial in purifying both physical and mental states, water as a purifier from the sky (rain), and the prohibition of khamr (which is intoxicating). The implementation of Abah Anom’s Inabah is similar to the janābah bath, or the bath performed after having major ḥadaś by reading special intentions and prayers. It is performed every morning at approximately 02.00 am in three stages: preparation, implementation, and closure. As a result of the data, it was concluded that Abah Anom's Inabah positively impacts patients in terms of self-awareness, cleanliness from toxins, and a sense of peace.